Peningkatan Hasil Belajar Keliling dan Luas Bangun Datar dengan Model Problem Based Learning di SD - Budi, Sentot Setia; Zainil, Melva (Universitas Negeri Padang, 2022)
The purpose of this research is to describe the learning outcomes improvement of circumference and area of two-dimentional figures by using problem based learning (PBL) models at Grade IV SDN 17 Manggis Ganting Bukittinggi. This type of research is Classroom Action Research using qualitative and quantitative approaches. The research subjects were teachers as observers, the researcher as practitioner, and 28 students of grade IV. The results of the first cycle study on the RPP an average of 82.81% (good), increased in the second cycle to 93.75% (very good). The implementation of the first cycle of teacher activity on average 82.14% (enough), increased in the second cycle to 96.42% (very good). Implementation of the first cycle of student activity on average 80.35% (enough), increased in the second cycle to 92.85% (very good). Student learning outcomes in the first cycle I meeting an average of 64.1 (C +), increased in the first cycle of meeting II to 69.2 (B-), increased in the second cycle to 76.25 (B +). Thus, it was concluded that the PBL model can improve mobile learning outcomes and flat build area in elementary schools.